Finishing properties of coffee table by using kelempayan (Neolamarckia cadamba) / Hanis Afiqah Idrus and Junaiza Ahmad Zaki - Idrus, Hanis Afiqah; Ahmad Zaki, Junaiza (2015)
Finishing is the most important part of manufacturing furniture process. The benefits of finishing are to give protection and attractive appearance on product itself. Finishing has two stages that are pre-finish and fully finish. Pre-finish is a preparation of surface product where it is must keep the product surface clean from dust, dirt, or any unwanted particle before applying the coating material. At this stage, sandpaper was also used to give smoothness to the product surface. Fully finish is a process of applying coating on the product. In this study, two types of system applying coating are used to compare the effect of finishing properties of a coffee table from Kelempayan. For system A, the process of sanding and sealer was repeated four times. Meanwhile, for system B, the process of sanding and sealer was repeated six times. The coating material use in this study is acid catalyst lacquer. The tests that have done are heat resistance test, household chemical resistant test, tape adhesion test and surface roughness test. Based on the results, its shows that the six layers of sanding sealer process give better results than four layers. But four layers are enough and more recommended because of saving cost and more economical.